What Makes the Indian Megacity Chennai’s Air Unhealthy? - A Bottom-up Approach to Understand the Sources of Air Pollutants - Poonam Mangaraj; Saroj Kumar Sahu; Gufran Beig; Ashirbad Mishra; Som Sharma (Aerosol and Air Quality Research)
Abstract In recent years, air quality in Indian megacities has emerged as the most pressing global concern, with Asian megacities being the most polluted. Unlike India’s pollution capital, Delhi, Chennai is a megacity significantly impacted by industrial and transportation activities and has been designated as a non-attainment city by the Government of India under the National Clean Air Programme. The first step towards sustained clean air is identifying the sources causing the megacity’s air quality to deteriorate. The current study is the first-ever attempt to develop bottom-up inventory at ultra-fine resolution (i.e., ~0.4 km × ~0.4 km), where the annual emission includes 39.6 Gg yr-1 of PM2.5, 65.0 Gg yr-1 of PM10, 387.3 Gg yr-1 of CO, 175.2 Gg yr-1 of NOx, 70.9 Gg yr-1 of SO2, 271.4 Gg yr-1 of VOC, 10.5 Gg yr-1 of BC, and 17.7 Gg yr-1 of OC for the base year 2020. This cutting-edge data on surface emissions with identified hotspots, would be vital tool for air quality studies and the first step towards framing mitigation strategies for sustainable air in Chennai.